Problem-driven iterative approaches and wider governance reform - and Rao, Sumedh (GSDRC, University of Birmingham, 2014)
Identify evidence which suggests that problem-driven, iterative approaches to public sector reform can deliver more substantial, wider, long-term governance reform.